Optimization of the software architecture of the virtual training system for warehouse workers training - Dedov, D.; Nikolyukin, M.; Kruglov, V.; Nikitnikov, Yu (AIP conference proceedings, 2023)
The implementation of virtual training systems is associated with the need to visualize and implement the technological processes of the subject area. These processes may include both the normal functioning of the equipment and the regular labor functions of the personnel, as well as activities in emergency situations and modeling of the abnormal state of the equipment and the environment. Often, the visualization of such processes leads to a significant computational load, which requires significant optimization of resources for correct operation within virtual reality systems. This paper describes the analysis of existing architectures used in the implementation of projects using the Unity game engine, which showed that the use of architectural patterns can increase the flexibility and readability of the program code, reduce its complexity, and improve the performance of the project as a whole. Approbation of the architecture was carried out on the example of a virtual simulator for training warehouse workers, in which it is necessary to model a large number of objects and organize interaction with them, as well as create the necessary visual effects to visualize emergency situations (for example, fires).